If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(r + -1) = -2 Reorder the terms: -2(-1 + r) = -2 (-1 * -2 + r * -2) = -2 (2 + -2r) = -2 Solving 2 + -2r = -2 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2r = -2 + -2 Combine like terms: 2 + -2 = 0 0 + -2r = -2 + -2 -2r = -2 + -2 Combine like terms: -2 + -2 = -4 -2r = -4 Divide each side by '-2'. r = 2 Simplifying r = 2
| (4-5x)/6=7 | | 16/15X=48 | | -7x+x-75=75 | | -10x+5=-9x-9 | | 8/3x+1/3x=4x+30/3+7/3x | | 1/2(6x-3)=-24 | | -3y-8=5y+12 | | 3x^2-42x+120=0 | | 11/6X=44 | | 16=x/5+5 | | -24b-16+25b-6=0 | | -4u^2+9u-3= | | 12-7x=-44 | | 3(y-3)+y=2(6+2y) | | 12x-4/3y=11 | | 1/4(32x-16)=6x | | 0.05/10 | | -8X-13=5X | | 0.2b+0.1=0.12b-0.06 | | (2x+5/7x-5)/(3x/7x-5) | | 9y-2-4y=-27 | | 4y+4=-2y-8 | | 0.19y+0.05(y+2000)=1540 | | 63d+63n=5.05 | | -21-x-2x=30 | | 9.12/x=0.2 | | 63(n+d)=5.05 | | 8t+1/9=t+9/18+t-7/18 | | 3xy+2x+3x= | | -(x+4)-2x+3=-16 | | 2x+3x+400=1050 | | 4b+3=2b |